Kode Vicious: System Changes and Side Effects. - Neville-Neil, George V. (Communications of the ACM, 2009)
In this article the author discusses switching build systems within the computer science industry, examining the complexity of Makefiles that exist in a build system. Topics include updating a legacy code, the benefits of switching a legacy system's build strategy, and Makefiles that are so complex that new users cannot modify them.